Geoconservation Initiatives in the State of Paraná (Brazil) - Luiz Alberto Fernandes; Fernanda Caroline Borato Xavier; Kimberlym Tábata Pesch Vieira; Liliane Maia Tcacenco-Manzano (Geoconservation Research)
Even though geoconservation has advanced significantly in the last few decades, general awareness of its importance is limited, especially in Brazil. Here, we present an overview of geoconservation actions and initiatives in the state of Paraná. We highlight geoscientific aspects since the 20th century, the installation of interpretative panels, and key findings from the inaugural geological heritage inventory for the state, the second in the country. We also present two examples of pioneering geoconservation and scientific communication initiatives: the creation of the Curitiba Sedimentary Basin geosite (a municipal conservation unit within the urban territory) and the Paleontology Museum of Cruzeiro do Oeste’s research station. Despite the concerted efforts of academic research groups, the state geological survey (Mineropar, now defunct) and the national geological survey (CPRM-SBG), current initiatives remain limited to academic research. Overall, there are not enough systematic public policies to protect the state and national geological heritage. Regrettably, geodiversity and geoconservation remain the least known components of the state's natural heritage. A long-standing concern has been the absence of geological content in the curriculum of the Brazilian basic education system. Overcoming this problem will require the incorporation of geology and geoconservation concepts into school curricula and educator training, and the effective communication of their significance to society at large.